Innate Immune Cytokine Profiling and Biomarker Identification for Outcome in Dengue Patients - Pradeep, Sai Pallavi; Hoovina Venkatesh, Pooja; Manchala, Nageswar R.; Vayal Veedu, Arjun; Basavaraju, Rajani K.; Selvasundari, Leela; Ramakrishna, Manikanta; Chandrakiran, Yogitha; Krishnamurthy, Vishwanath; Holigi, Shivaranjani; Thomas, Tinku; Ross, Cecil R.; et al. (Frontiers in Immunology, 2021)
Background: Early biomarkers of progression to severe dengue are urgently required to enable effective patient management and control treatment costs. Innate immune cells which comprise the earliest responders to infection and along with the cytokines and chemokines they secrete play a vital role in orchestrating the subsequent adaptive immune response, have been implicated in the enhancement of infection and “cytokine storm” associated with dengue severity. We investigated the early innate immune cytokine profile of dengue patients during acute phase of disease in a prospective blinded study that included subjects with acute dengue and febrile controls from four major hospitals in Bengaluru, India along with healthy controls. We used intracellular cytokine staining and flow cytometry to identify innate immune biomarkers that can predict progression to severe dengue. Results: Dengue infection resulted in enhanced secretion of multiple cytokines by all queried innate immune cell subsets, dominated by TNF-α from CD56+CD3+ NKT cells, monocyte subsets and granulocytes along with IFN-γ from CD56+CD3+ NKT cells. Of note, significantly higher proportions of TNF-α secreting granulocytes and monocyte subsets at admission were associated with mild dengue and minimal symptoms. Dengue NS1 antigenemia used as a surrogate of viral load directly correlated with proportion of cytokine secreting innate immune cells and was significantly higher in those who went on to recover with minimal symptoms. In patients with secondary dengue or those with bleeding or elevated liver enzymes who revealed predisposition to severe outcomes, early activation as well as efficient down-regulation of innate responses were compromised. Conclusion: Our findings suggested that faulty/delayed kinetics of innate immune activation and down regulation was a driver of disease severity. We identified IFN-γ+CD56+CD3+ NKT cells and IL-6+ granulocytes at admission as novel early biomarkers that can predict the risk of progression to severity (composite AUC = 0.85-0.9). Strong correlations among multiple cytokine-secreting innate cell subsets revealed that coordinated early activation of the entire innate immune system in response to dengue virus infection contributed to resolution of infection and speedy recovery.